ARCHIVE STORAGE OF DOCUMENTS UNDER THE CONDITIONS OF THE TRANSITION TO ELECTRONIC DOCUMENT MANAGEMENT - GRYNCHYSHYN, Petro (Scientific journal «World of Finance», 2025)
Introduction. The introduction of electronic document management significantly reduced the volume of paper documents and, at the same time, raised the issue of information storage. The threat of document loss arising during martial law further strengthens the need to find ways to solve the problem of preservation and safe access to information that is valuable to the state. The relevance of the study lies in the need to highlight the prospects for the introduction of electronic archiving for information on the execution of budgets.The purpose of the article is to analyze the normative regulation of archival matters, the impact of the introduction of electronic document management in the budget sphere on the volumes of stored information and outline the prospects for the use of electronic archives for storing data that accumulates during the implementation of budgets.Results. The analysis of the legal framework regulating archival storage of data and work with electronic documents showed that it establishes and defines only the transfer of electronic documents to the archive, but the issue of the work of archives that store electronic documents remains neglected. The tendency to reduce documents in paper form after the implementation of the system of remote treasury service of managers and recipients of budget funds was demonstrated.Conclusions. The need to introduce electronic archives to preserve information on budget execution is substantiated, which will ensure: reliable storage of documents in accordance with the requirements of current legislation; organization of search and access to necessary information; a high degree of data protection of managers and recipients of budget funds.